Researching as a Commoner: Affect and the Lives of Underprivileged Mobile Youth in Greece - Stelios Pantazidis; Yannis Pechtelidis (Social Sciences)
This paper examines the role of commons-based activist ethnography in reshaping the dynamics between researchers and underprivileged mobile youth (UMY), focusing on the opportunities and ethical challenges of this approach. Conducted in youth centers in Thessaloniki, Greece, the study explores how trust, affect, and collaborative knowledge creation supported agency among UMY while confronting systemic barriers and power asymmetries. Using qualitative ethnographic methods, the research investigates the role of convivial spaces and the ambiance of the commons in creating meaningful connections and emotional resilience, enabling the participants to articulate aspirations and reclaim agency. The dual role of the researcher as an advocate and observer raised questions about representation and power dynamics. This paper contributes to discussions on activist ethnography by offering insights into its possibilities and limitations in advancing transformative research with marginalized populations.